Design and construction of a 273Mld water treatment plant using immersed membrane technology - Ooi, Oon Hee. (2008)
To share the experience in the design and construction of the first water treatment plant using membrane technology in Singapore, including the design considerations stage to the supervision of the construction of the various treatment facilities and the problems encountered.